Effect of Drying and Broccoli Leaves Incorporation on the Nutritional Quality of Durum Wheat Pasta - Natalia Drabińska; Mariana Nogueira; Ewa Ciska; Henryk Hubert Jeleń (Polish Journal of Food and Nutrition Sciences)
Pasta is a great vehicle for the incorporation of vegetable-derived ingredients to increase the consumption of the health-beneficial components originating from vegetables. Notably, by-products of vegetable processing can also serve as a rich source of phytochemicals. An important step in pasta processing is drying which can affect the content of bioactive compounds in pasta. This study aimed to evaluate the effect of drying on the nutritional quality and cooking properties of durum wheat pasta fortified with broccoli leaves. Pasta enriched with broccoli leaf powder (BLP) at 2.5% (B2.5) and 5% (B5), and control pasta without BLP (C), which differed in drying conditions: fresh pasta without drying (F), pasta dried at 50 o C for 8 h (L), and pasta dried at 80 o C for 3 h (H) were formulated. The obtained pasta products were analysed for the cooking properties (optimal cooking time, cooking loss, water absorption and swelling capacity); colour parameters; proximate composition; and contents of free amino acids (FAA), fatty acids and sugars. BLP significantly improved the contents of ash by up to 35 g/100 g, FAA and fatty acids to up to 1298 nmol/g dry matter (DM) and 16741 µg/g DM, respectively, without compromising the cooking quality of pasta. Drying had a significant effect on fatty acids, which content in pasta processed at the highest temperature tested decreased. From the nutritional point of view, the low-temperature drying seems to be an interesting method for pasta preparation, with the highest content of FAA, fatty acids, especially unsaturated ones, and the lowest content of sugar. However, at the same time, the dried pasta products were characterised by greater cooking loss approximating 10%.